Herbal Medicine for Behavioral and Psychological Symptoms of Dementia: A Systematic Review and Meta-Analysis - Kwon, Chan-Young; Lee, Boram (Frontiers in Pharmacology, 2021)
Background: Dementia is a global health concern, causing serious health and socioeconomic burdens with population aging. The associated symptoms of dementia, called behavioral and psychological symptoms of dementia (BPSD), are factors contributing to the socioeconomic burden of dementia. Recently, herbal medicine (HM) has attracted attention as a potential complementary therapy for BPSD. Therefore, this systematic review was aimed at analyzing the effectiveness (or efficacy), safety, and research status of HM in BPSD management through a comprehensive review. Methods: Thirteen electronic databases were searched comprehensively. Related clinical studies published until December 28, 2020, were collected. The methodological quality was evaluated using tools such as the Cochrane Collaboration’s risk of bias tool according to the study design. The effectiveness (or efficacy) was analyzed for randomized controlled trials (RCTs) only, and when sufficient homogeneity was assured, effect estimates were presented as mean difference (MD) and risk ratio (RR), with 95% confidence interval (CIs), through a meta-analysis. Results: A total of 52 clinical studies, including 36 RCTs, were included in this review. As an adjunctive therapy, HM showed statistically significant benefits in BPSD severity assessed by the Behavior Pathology in Alzheimer’s Disease Rating Scale (combined with psychotropic drugs: MD = −3.48, 95% CI: −3.96 to −2.99; with anti-dementia drugs: MD = −2.81, 95% CI: −3.17 to −2.45) and Neuropsychiatric Inventory (with anti-dementia drugs: MD = −3.23, 95% CI: −4.06 to −2.40). Adverse events were significantly less frequent in the HM group (RR = 0.50; 95% CI: 0.28 to 0.88). However, the methodological quality of the RCTs included in this systematic review was not optimal overall. Conclusion: According to the findings of this review, HM may be associated with additional benefits in BPSD treatment, particularly when used as an adjunct to conventional medications, including psychotropic and anti-dementia drugs. However, considering the methodological quality of the included RCTs, this clinical evidence is not robust. Nevertheless, dementia is a global health concern, and considering the limitations of conventional psychotropic drugs for BPSD, a major cause of the disease burden, HM appears to be a promising complementary therapy that warrants further research.